Komunikasi Edukasi Dampak Kecanduan Games bagi Siswa SMAN Batusangkar Sumatera Barat - Rahmi Surya Dewi; Ernita Arif; Sarmiati Sarmiati; Diego Diego; Annisa Anindya; Rinaldi Rinaldi (Warta Pengabdian Andalas, 2019)
This community service activity is motivated by the phenomenon of the high number of addicting playing online games for the younger generation (students) today. This condition is inseparable from the development of technology and the availability of various applications and other factors originating from these students. The presentation and appearance of these online games are usually very interesting, thus causing the attraction of the player, and favored by various groups ranging from children to adults. However, interest and pleasure in playing this online game causes people to forget themselves, forget time, and there is always a sense of curiosity so that they want to play the game continuously (addicted). The impact of this online gaming addiction is a decrease in front brain waves that have an important role, behave aggressively, get angry easily, have multiple personalities, have problems in social relations, lie, misuse of money to decrease productivity and physical health due to long exposure to computer radiation or gadgets. This activity aims to increase students' knowledge about the effects of online gaming addiction. This activity was carried out in the form of counseling and combined with the introduction of making animation as a smart form in using gadgets. The enthusiasm of students and the support of the school was very large as seen from the many students who asked and participated in the event. In addition, the school also welcomed the comments that information on the use of gadgets is very important at this time not only for students but also for adults to be smart in using it. The school also requested that extension activities and similar training can be carried out again in the future.